THE ROLE OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP IN THE SUSTAINABLE ECONOMIC DEVELOPMENT OF REGIONS - Khujakulova, Nigora Rustamovna (THE INNOVATION ECONOMY, 2026)
This article discusses the role and importance of small business and private entrepreneurship in ensuring sustainable economic development of regions from a scientific, theoretical and practical perspective. The impact of small business entities on the regional economy, their role in increasing employment, increasing incomes, diversifying production and stimulating innovative activity are analyzed. Institutional, financial and infrastructural factors affecting the development of small business and private entrepreneurship in the regions are also studied. Scientific and practical proposals and recommendations are developed to improve mechanisms for supporting small business and private entrepreneurship in the regions.